ASEAN’s Migrant Rights Policy Dilemma and Deadlock on Migrant Worker Protection - Agusmidah, Agusmidah; Martono Anggusti; Fithriatus Shalihah; Rajali H. Aji; Abdulrahman Sama-Alee (Lembaga Contrarius Indonesia, 2025)
Remittances generated by migrant workers, particularly those from Indonesia, play a significant role in supporting the economic stability of households and national economies. However, the magnitude of these contributions contrasts sharply with the limited legal and social protection available to migrant workers. This research examines the key factors underlying the persistent impasse in migrant worker protection policies within ASEAN and explores potential strategies for improvement through a comparative assessment of the European Union experience. Using normative juridical methods that combine conceptual, regulatory, and comparative analyses, the study evaluates ASEAN legal instruments and compares them with the European Union framework for protecting migrant workers. The analysis identifies three main causes of policy stagnation in ASEAN. First, the region lacks binding obligations that require member states to adopt uniform minimum standards. Second, existing enforcement mechanisms are weak and do not ensure consistent implementation. Third, member states resist the establishment of supranational authority, limiting opportunities for stronger regional governance. Despite these challenges, functional adaptation through the selective adoption of European Union practices offers viable options, including harmonizing minimum standards, establishing regional complaint procedures, and facilitating the portability of social rights. The research concludes that a gradual and priority based approach, especially for high risk sectors, can enhance migrant worker protection while remaining consistent with the principles of the ASEAN Way.